Analisis Penerapan Metode Moora dalam Seleksi Penerimaan Beasiswa Mahasiswa - Badriah Nursakinah; Habib Nurfaizal; Khairudin (LPPM STMIK IKMI Cirebon, 2025)
Scholarship acceptance is an important instrument in supporting the success of higher education, both to motivate outstanding students and to help those who are less fortunate. However, the selection process is often constrained by the objectivity, transparency, and complexity of decision-making because it involves various criteria. This research offers a solution by applying the Multi-Objective Optimization based on Ratio Analysis (MOORA) method, which is able to process multicriteria data by distinguishing benefit and cost criteria so as to produce an objective ranking. The purpose of this study is to analyze the application of the MOORA method in the selection of student scholarship admissions and assess its effectiveness in supporting decision-making. The study used five criteria, namely GPA, parental income, achievement, number of family dependents, and organizational activeness. The calculations are done using the Python programming language. The results of the study show that Rina Amelia ranks first with the highest MOORA score. These findings prove that the MOORA method is effective, transparent, and can be an alternative solution for universities in the scholarship selection process.